Developing Blended Learning Model in Vocational Education Based On 21st Century Integrated Learning and Industrial Revolution 4.0 - et. al., Nizwardi Jalinus, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to develop a blended learning model in vocational education. This research used the stages of ADDIE model. The research was carried out at Universitas Negeri Padang, Indonesia. The instruments used were questionnaires, observation sheets, and cognitive, affective, and psychomotor tests. The results were (1) Blended learning models include: (a) the philosophical component of essentialism and pragmatism; (b) learning theory: behaviorism, cognitivism, and connectivism (c) the 4C component of communication, collaboration, cooperation, and creativity; (d) component of the industrial revolution 4.0: includes learning with digital elements with data literacy, technological literacy, and human literacy. (2) The blended learning model is centered on learning done offline and online makes it has a clear proportion of learning patterns. The flexibility of learning anytime and anywhere through face-to-face communication, as well as online interactions using online chats and forums to explore critical thinking through discussion. It also includes elements of students to be creative and innovative in projects and project improvement, as well as online teaching materials that are made interesting by the presence of multimedia components (text, images, and videos). (3) The result product is in the form of a model book, lecturer manuals and student guides, and textbooks, which are declared valid and practical so that the blended learning model can be applied in learning. (4) The achievements found are related to cognitive, affective, psychomotor and 4C abilities.